Anatomy of stem and root of Ipomoea cairica (L.) Sweet (Convolvulaceae) - the Lianescent Vascular Syndrome - Martins, Mailson Santos; Guedes, Maria Lenise da Silva; Dias Leme, Claudia Luizon (Balduinia, 2021)
Anatomy of stem and root of Ipomoea cairica (L.) Sweet (Convolvulaceae) - the Lianescent Vascular Syndrome. Among the Ipomoea species of economic importance, the liana Ipomoea cairica stands out because of its great pharmacological potential. Considering that the cambial variant present in Ipomoea is not causally related to the habit, the aim of this study is to list the group of anatomical features that define the “lianescent vascular syndrome” in the species, as well as to verify if there is variation between the stem and the root anatomy. Transverse and longitudinal sections of fresh material were analyzed qualitatively and quantitatively. Thus, it was found that the anatomy of the secondary xylem of I. cairica is similar to that of other species of Ipomoea, including indistinct growth rings, diffuse and porous vessels mainly solitary, simple perforation plate, alternate bordered pit, tyloses, heterocellular mainly uniseriate rays, and non-lignified parenchyma. The characteristics of the “lianescent vascular syndrome” is related to the high percentage of parenchyma. However, statistical analysis showed differences between stem and root in vessel diameter and vessel frequency, with higher values of vessel diameter and lower values of frequency of vessels in the root secondary xylem. These differences must be related to the environment in which the organ develops, as well as to the mechanisms involved in water conduction. Specific studies will make possible to test this hypothesis.